"Listen, did you hear…?" A structural equation model explaining online information sharing on the risks of nanotechnology in food. (September 2019) - Kuttschreuter, Margôt; Hilverda, Femke
Highlights: Enabling online information sharing means to encourage informed decision making. Model explaining online information sharing based on TPB and RISP. Evaluated model explained 41% of variance in online information sharing. Injunctive norms most important determinant predicting information sharing. Attitude to share and information seeking significant proximal determinants. Abstract: In order to encourage consumer informed decision making, it is in the interest of risk communicators in the food industry and authorities to facilitate consumer risk information sharing. Focusing on the risks of nanotechnology in food products, this study aimed to develop and test a model that describes the processes that result in the online sharing of risk information on food products. The model was based on the Theory of Planned Behaviour, the Risk Information Seeking and Processing model and the broader risk perception and communication literature. A cross-sectional online survey has been carried out among a representative sample of adults >18 years of age in the Netherlands (n = 511). Attitude, self-efficacy, and injunctive and descriptive subjective norms in relation to information sharing were measured, as were information need, information seeking, trust, risk perception and anxiety in relation to the application of nanotechnology in food products. Structural equation modelling (SEM) was applied to test the determinants of information sharing behaviour, and their relationships. Results showed that the intention to share information about the risks of nanotechnology in food online was medium-low. The hypothesized model as a whole fitted the data and nine of the fourteen path coefficients were highly significant. Results showed injunctive norms to be the main determinant of information sharing. Attitude and information seeking also contributed to the explanation of the variance in information sharing. Results are put into the perspective of relevant theoretical viewpoints and empirical findings. Implications for food risk communication and the facilitation of informed decision making are discussed.